Comparison of 24% sucrose as analgesic during 2nd and 3rd diphtheria-pertussis-tetanus vaccinations with 1st diphtheria-pertussis-tetanus vaccination - Kavthekar, Saiprasad Onkareshwar; Bharati, Hemant Pralhad; Kurane, Anil Bapurao; Patil, Rahul Ravaso (Indian Journal of Child Health, 2017)
Background: International clinical guidelines recommend oral sucrose to be given to relieve procedural pain in neonate. Objective: The aim of this is to study analgesic effect of 24% sucrose beyond neonatal age up to 4 months by comparing its effect during the 2nd and 3rd diphtheria-pertussis-tetanus (DPT) vaccinations with the 1st DPT. Materials and Methods: This prospective study was conducted in 150 healthy infants undergoing for their 1st, 2nd and 3rd DPT vaccination of 50 each and received 24% Sucrose 2 ml 2 min before vaccination. The outcome variables were total duration of cry, first cry, change in heart rate and modified facial coding score (MFCS). The data were analyzed statistically. Results: Mean total duration of cry was significantly longer in 3rd DPT 94.4 (30.12) s and 2nd DPT babies 50.6 (26.14) s than 1st DPT babies 36.3 (25.34) s. Mean duration of the first cry was significantly higher in 3rd DPT 52.1 (13.12) s and 2nd DPT babies 37.3 (15.14) s than 1st DPT babies 18.2 (14.12) s. Mean change, that is, rise in heart rate (beats/min) from baseline was significantly higher in 3rd DPT 16.6 (4.9) and 2nd DPT babies 10.3 (5.2) than 1st DPT babies 3 (2.3) Change in median MFCS at 1 and 3 min was significantly higher with 3rd DPT (3, 2) and 2nd DPT (2, 1) groups as than 1st DPT (1, 0). Longer mean total and first cry, and increase in heart rate was maximum in 3rd DPT group. Conclusion: Nearly 24% sucrose had less analgesic activity in babies receiving 3rd and 2nd DPT vaccination compared to those receiving 1st DPT, and it suggested 24% sucrose had less analgesic effect between 2 and 4 months of age babies.